Genomic and functional insights into pathogenicity of Ascochyta rabiei - Mahmuda Binte Monsur; Ido Bar; Rebecca Ford (Journal of Plant Pathology, 2026)
Ascochyta rabiei , the causal agent of Ascochyta blight in chickpea, is a necrotrophic fungus of major economic concern across chickpea-growing regions worldwide. Advances in genome sequencing and transcriptomic profiling have revealed a large set of putative pathogenicity-related genes in the A. rabiei genome, including effectors, secondary metabolite clusters, and carbohydrate-active enzymes. However, most of the candidate pathogenicity genes remain as computational predictions, with only a handful having been functionally validated. This limits the ability to directly link allelic diversity with pathogenicity and hinders the development of molecular tools for screening for isolate pathogenicity. This review synthesizes recent genomic, transcriptomic, and functional studies on A. rabiei , with a particular focus on effector biology, immune evasion strategies, and current functional genomics approaches. Knowledge gaps are highlighted, including bioassays at mature plant stages, and the absence of molecular functional validation of pathogenicity related sequences in this species. Addressing these challenges will be critical for moving from having just gene catalogues to deeper functional understanding of pathogenicity associated sequences, towards an improved understanding of A. rabiei pathogenicity and potential for future effector-informed breeding strategies.